Cytogenetic characterization and B chromosome diversity in direct-developing frogs of the genus Oreobates (Brachycephaloidea, Craugastoridae) - Ferro, Juan Martín (2016)
Oreobates Jiménez de la Espada, 1872 is a South American frog genus within the superfamily Brachycephaloidea, a large group of frogs with terrestrial reproduction and direct development. About 260 brachycephaloidean species have been cytogenetically studied so far, at least with standard techniques. However, this information represents fewer than 17% species of the family Craugastoridae Hedges, Duellman and Heinicke, 2008, where the genus Oreobates is included. In the present work, using a diversity of standard and molecular techniques, we describe the karyotype of O. barituensis Vaira and Ferrari, 2008, O. berdemenos Pereyra, Cardozo, Baldo, and Baldo, 2014 and O. discoidalis (Peracca, 1895), from northwestern Argentina. The three species analyzed showed a diploid karyotype with 2n = 22 biarmed chromosomes, fundamental number (FN) = 44, nucleolus organizer regions (NORs) located pericentromerically on pair 7, and a centromeric and perocentromeric C-banding pattern. We observed variations in the chromosome number in O. barituensis due the presence of two morphs of B chromosomes, one medium-sized telocentric (BT) and another subtelocentric and smaller (Bst). Both B chromosomes are mitotically stable and were recorded in all somatic and germinal cells analyzed. The BT chromosome occurred at a maximum of one per individual (2n = 22+BT), and the other one was observed single (2n = 22 + Bst) or as a pair in two doses (2n = 22 + 2BT). We additionally observed other supernumerary chromosomes in the three species analyzed, all of them euchromatic, small, dot-shaped and with instability during mitoses, showing a frequency of occurrence below 50% in studied specimens. The occurrence of polymorphic and spontaneous chromosomal rearrangements and supernumerary chromosomes is a recurrent feature reported in frogs with terrestrial habits (Brachycephaloidea and Hemiphractidae Peters, 1862), which suggests that Brachycephaloidea may be a promising group for studying the origin and maintenance of B chromosomes in anurans.